2022
DOI: 10.1007/s10763-022-10340-z
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Science: Schoolteachers’ Motivation, Experiences, and Recommendations

Abstract: Citizen science offers teachers a way to bring authentic scientific research into their classrooms by providing both teachers and their students with opportunities to contribute to authentic research. The potential of citizen science for science education has already been highlighted in various fields and by various stakeholders. More and more studies underpin this potential by providing evidence for the learning outcomes achieved through participation in citizen science projects. In formal education settings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In Project M, conversations with teaching staff directly impacted the protocol and the strategy, where they shared the need for connections to the curriculum and science education learning outcomes (Kelemen-Finan et al, 2018;Scheuch et al, 2018;Roche et al, 2020;Aristeidou et al, 2022). The division between science education and science communication in the classroom and in research can imply that they have little in common, when the reality is that they fundamentally share the common goals of education, entertainment and engagement in and about science (Baram-Tsabari and Osborne, 2015).…”
Section: Co-creating the Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In Project M, conversations with teaching staff directly impacted the protocol and the strategy, where they shared the need for connections to the curriculum and science education learning outcomes (Kelemen-Finan et al, 2018;Scheuch et al, 2018;Roche et al, 2020;Aristeidou et al, 2022). The division between science education and science communication in the classroom and in research can imply that they have little in common, when the reality is that they fundamentally share the common goals of education, entertainment and engagement in and about science (Baram-Tsabari and Osborne, 2015).…”
Section: Co-creating the Protocolmentioning
confidence: 99%
“…Frequent reality checks are critical to ensure what you are proposing is possible for the target audience. There is often a gap between what people sign up for and what they think they are signing up for, as well as a gap between the expectation and reality of resource and time availability in schools (Aristeidou et al, 2022). This is particularly true when thinking about school laboratories/equipment or access to computers or printers.…”
Section: Co-creating the Protocolmentioning
confidence: 99%
“…Alongside learning of science content and practices, teachers often underscore additional beneficial effects of students' engagement with authentic science investigations. Teachers typically believe that helping to solve a real‐world scientific problem has an important role in: (a) motivating students (Aristeidou et al, 2022; Doyle et al, 2018, 2019; Kaplan Mintz et al, 2021), (b) enriching students' perspectives about their own identity and work (Bracey, 2018; Rushton & Reiss, 2019), (c) building students' science identity (Bracey, 2018; Doyle et al, 2019; Kaplan Mintz et al, 2021; Rushton & Reiss, 2019), and (d) enhancing students' capacity for agency and action (Atias et al, 2023; Bracey, 2018; Kaplan Mintz et al, 2021). The studies demonstrating these findings were conducted mostly in the context of contributory projects, illustrating that teachers expect and encounter such outcomes even as students participate in limited roles within the scientific research.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Citizen science projects provide both problem-oriented and project-oriented learning experiences that can be integrated into formal and non-formal education settings. Several studies have indicated that citizen science programs can be effective learning activities when incorporated into the classroom (Aristeidou et al, 2022;Godfrey et al, 2022;Lüsse et al, 2022). By incorporating citizen science into general education, educators can provide authentic research experiences while reducing resource consumption (Vitone et al, 2016).…”
Section: Constructivism Learning Theorymentioning
confidence: 99%